Analysis of near cortex versus both cortex screw fixation in bone fracture surgery - Ang, Li Juan (2014)
Bone fractures are common due to accident and falls. The current-state of the art of stabilizing a fracture is by using of Locking Compression Plates (LCPs). Accelerated healing can occur when the blood supply to bone is taken care of.